Assessment of Serum Phosphate in Patients with Acute Respiratory Distress Syndrome on Mechanical Ventilation and Its Effect on Disease Severity and Mortality - Emad Abbas, Zahraa; Ali Hashim Ibrahim, Jehan (South Asian Journal of Social Sciences and Humanities, 2025)
Background: Acute respiratory distress syndrome (ARDS) is a severe form of respiratory failure, life-threatening condition, characterized by rapid onset of widespread inflammation in the lungs and severe hypoxemia with significant impact on the morbidity and mortality of critical care patients who have a high prevalence of hypophosphatemia because of the presence of multiple causal factors . Identification of prognostic biomarker for ARDS as serum phosphate may aid in improving survival. Objective of the study: Evaluate role of hypophosphatemia in disease severity and mortality. Method: prospective study was conducted from 1st of October 2018 to1sof June 2019, on Fifty subjects with ARDS on mechanical ventilation in the intensive care units (ICUs) of medical city hospitals in Baghdad, variable ages, variable risk factors. Serum phosphate level measured for all study sample. Results: Fifty patients with ARDS, 26%mild 50%moderate 24%severe severity, 56% female versus 44% male. The mean age for ARDS was 49.56 ± 20.31 years, aged >50 years (48%). Pneumonia (28%) was common risk factor. 30% hypophosphatemia versus 6% hyperphosphatemia. 60% of study patients were died. There was no significant association between severity of ARDS and S. Phosphate level (P ≥ 0.05). There was significant association between prevalence of mortality and S. Phosphate level (P ≤ 0.05). The cut point of S. Phosphate was 3.1 mg/dL, S. Phosphate < 3.1 mg/dL is predicator for risk of mortality as a large significant area under the curve (AUC= 71.5%) indicating significant association between S. Phosphate level and risk of mortality. S. Phosphate was 80% sensitive, 60% specific, and 72% accurate as a predictor for risk of mortality. Conclusion: Patients with ARDS have low serum phosphate level tend to increase mortality rate. Evaluation the serum phosphate concentration carefully and early detection of hypophosphatemia in patients with ARDS and correcting it to within normal range if possible.